Implementation of a bit permutation-based advanced encryption standard for securing text and image files - Heidilyn V Gamido (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The paper proposes a modification of the advanced encryption standard (AES) to address its high computational requirement steaming from the complex mathematical operations in the MixColumns Transformation which makes the encryption process slow. Bit Permutation was used instead of the MixColumns Transformation since the use of bit permutation in an encryption algorithm achieves efficiency by providing minimum encryption time and memory requirement. Results of the study showed that the modified AES algorithm exhibited faster encryption by 18.47% and faster decryption by 18.77% for text files. The modified AES algorithm also resulted to 16.53% higher avalanche effect compared with the standard AES thus improving the security performance. Application of the modified AES in encrypting images in Cipher Block Chaining mode showed that the modified algorithm also exhibited 16.88% faster encryption and 11.96% decryption compared with the standard AES. Likewise, modifying the algorithm achieved the ideal result in the histogram analysis, information entropy, the correlation coefficient of adjacent pixels to resist statistical attack.  The ideal value in number of pixels change rate and unified average change intensity were also achieved making the modified algorithm resistant to differential attack. These results show that modifying AES by using bit permutation to replace MixColumns Transformation was able to address the high computational requirement of the algorithm resulting in a faster and more secure encryption algorithm for text files and images.